Adjustment of Online Learning: The Problem Experienced by Parents, Teachers, and Students during the Covid-19 Pandemic - Sahari Sahari; Ishak Talibo; Nurhayati Nurhayati; Rosdalina Bukido (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to identify problems experienced by teachers, parents, and students in online learning during the COVID-19 period and examine students' completeness in learning without physical interaction with teachers. This research was conducted at MIN 2 and MI al-Amanah Bailang Manado. There were 16 informants: 4 teachers, 6 parents and 6 students. Interview was conducted directly and by telephone. The results showed that while students were at home learning during Covid-19 some parents paid attention and help their children to study. The parents find it difficult to accompany their children to study at home. It is due to their busyness and their inability and knowledge to explain their children’s subjects. Completeness of teaching and learning in online learning without physical interaction make the teachers must be concerned about the condition of their students. The students are 'forced' to learn through online media while they do not have adequate facilities at home. Teachers find teaching using online media difficult. It is due to limited ability in using applications such as zoom, e-learning, cloud, whatsapp, and others. Some teachers are not ready to conduct online learning. During the covid-19 period, the student will study if the teachers give an assignment. The parents’ supervision makes their children uncomfortable to study at home.